2021
DOI: 10.11591/ijere.v10i3.21671
|View full text |Cite
|
Sign up to set email alerts
|

The cloud computing systems’ adoption in the higher education sector in Oman in light of the COVID-19 pandemic

Abstract: <p><span>The objective of the research was to find out the key factors that influence the acceptance and usage of cloud computing systems in the Omani higher education sector, with special emphasis on the COVID-19 outbreak. For this purpose, a quantitative research approach was conducted where 200 students from several Omani higher education institutions were surveyed, and by using Partial Least Square (PLS) to analysis the collected data. The findings revealed that the intention to use cloud compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 18 publications
3
4
0
Order By: Relevance
“…Notably, in contrast to Perceived Usefulness (PU), the influence of PEOU (β = 0.513) emerges as more pronounced on MCC adoption. These findings align with expectations and corroborate with analogous empirical studies conducted in a comparable context (Al-Hajri et al, 2021;Oliveira et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Notably, in contrast to Perceived Usefulness (PU), the influence of PEOU (β = 0.513) emerges as more pronounced on MCC adoption. These findings align with expectations and corroborate with analogous empirical studies conducted in a comparable context (Al-Hajri et al, 2021;Oliveira et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the empirical evidence supports the argument that the intention to adopt mobile cloud computing is positively influenced by the users' beliefs regarding its usefulness. Similar studies and research in the field of IS/IT adoption have also found that perceived usefulness significantly affects cloud computing adoption (Al-Hajri et al, 2021;Almaiah & Al-Khasawneh, 2020;Hussein Alghushami et al, 2020). The results suggest that universities recognize the potential benefits of mobile cloud computing, such as enhancing students' academic performance and providing access to learning materials anytime and anywhere.…”
Section: Discussionsupporting
confidence: 62%
“…Other research by Lee et al [21] provided suggestions on how to effectively implement synchronous online reverse learning in teacher training programs during COVID-19, which can be leveraged in regular basic education in Peru as long as the education system is digitized. Also in the research conducted by Al-Hajri et al [22] aimed to discover the key factors influencing the acceptance and use of cloud computing systems in the education sector, with special emphasis on the outbreak of COVID-19. The findings revealed that the intention to use cloud computing in this context depends significantly on its perceived ease of use, usefulness, perceived reliability, and responsiveness.…”
Section: Being Unprepared For New Challenges In the Pandemicmentioning
confidence: 99%
“…The novel Coronavirus 2019 (COVID-19) outbreak was officially reported by Wuhan City Health Committee, China, on December 31, 2019 (Al-Hajri et al , 2021). Since then, many cases were reported and officially an epidemic was announced in China.…”
Section: Introductionmentioning
confidence: 99%